2018
DOI: 10.1089/ten.tea.2017.0358
|View full text |Cite
|
Sign up to set email alerts
|

Bone Regeneration of Osteoporotic Vertebral Body Defects Using Platelet-Rich Plasma and Gelatin β-Tricalcium Phosphate Sponges

Abstract: The objective of the present study was to investigate the effect of platelet-rich plasma (PRP) combined with gelatin β-tricalcium phosphate (β-TCP) sponge on bone generation in a lumbar vertebral body defect of ovariectomized rat. After creating critical-size defects in the center of the anterior vertebral body, the defects were filled with the following materials: (1) no material (control group), (2) gelatin β-TCP sponge with PRP (PRP sponge group), and (3) gelatin β-TCP sponge with phosphate-buffered saline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…Risk of bias of animal studies was high for almost all the examined studies. Among the 13 included in vivo studies, three for PLT functions during OP and 10 for PLT derivatives in OP, 10 of them have not declared the method of sequence generation [41,42,[49][50][51][52][53]56,57], in one study the method was unclear [55] and in the remaining two studies the method of sequence generation was clearly declared [40,58]. The majority (n = 7) of the studies showed that groups were similar concerning baseline characteristics (i.e., age, weight, sex) and two studies showed that allocation was adequately concealed [40,58].…”
Section: Assessment Of Methodological Qualitymentioning
confidence: 99%
See 4 more Smart Citations
“…Risk of bias of animal studies was high for almost all the examined studies. Among the 13 included in vivo studies, three for PLT functions during OP and 10 for PLT derivatives in OP, 10 of them have not declared the method of sequence generation [41,42,[49][50][51][52][53]56,57], in one study the method was unclear [55] and in the remaining two studies the method of sequence generation was clearly declared [40,58]. The majority (n = 7) of the studies showed that groups were similar concerning baseline characteristics (i.e., age, weight, sex) and two studies showed that allocation was adequately concealed [40,58].…”
Section: Assessment Of Methodological Qualitymentioning
confidence: 99%
“…All studies used PRP as PLT products with the exception of a study which used L-PRF [58]. Six of these studies (60%) also employed a scaffold/biomaterial (calcium phosphate, calcium aluminate/calcium aluminate-melatonin, β-tricalcium phosphate, bovine bone graft, nanoporous TiO 2 , hemostatic sponge) to incorporate the PLTs derivatives and subsequently evaluated bone regeneration in calvaria [51,58], tibia [54,56] and in caudal and lumbar vertebrae [53,57]. Clafshenkel et al [51] evaluating a calcium aluminate and calcium aluminate-melatonin scaffolds implanted in a critical size calvaria defect of OVX rats, showed that the addition of PRP did not significantly improve degree, intensity and abundance of osteoid tissue mineralization and bone formation in either of the two scaffolds [51].…”
Section: Platelet Derivatives In Osteoporosismentioning
confidence: 99%
See 3 more Smart Citations